Research on the construction of teaching staff in private colleges and universities under the background of “double first class” - Wang Lina; Chen Mei (ITM Web of Conferences, 2022)
The construction of “Double First Class” opens a new journey of building a Powerful Country in Higher Education. As an important part of higher education, private colleges and universities also undertake the important mission of talent training. The construction level of the teaching staff of private colleges and universities directly affects the smooth implementation of the national “double first-class” construction. The number of private universities in Shandong ranks among the top in the country. Taking Shandong Province as an example, this paper conducts a research on the construction of the teaching staff of private universities from the aspects of the current situation, problems encountered, problem analysis and countermeasures of the teaching staff of private universities.